Use of Agada Preparation in the Current Scenario- A Review Article - Sharma, Sukriti; Singh, Jaram; Kaur, Kulwinder; Kumar, Sanjeev (International Research Journal of Ayurveda & Yoga, 2022)
Background: In current scenario, maximum diseases are caused due to idiosyncratic etiology. Agada Tantra is one of the eight branches of Ayurveda which focusses on Viruddhaahara (Incompatible food), Gara Visha (Concocted poison) and Dushivisha (Denatured/Latent Poison), conditions and their treatments. There are different types of Agada yogas that are mentioned in the Vishachikitsa granthas which possess antitoxic properties, antioxidant activities can be very useful in such disease condition. In today’s era we need complete Nirvishikarana (Detoxification) because many of the diseases are caused due to cumulative, concocted, and incompatible dietary habits. So, Agada yogas need to be evaluated and given in these conditions. Aim: To evaluate the effect of Agada Yogas for their capabilities to be adopted in the diversified field of toxicology and in current scenario. Materials & Methods: Reviewed from various text books, databases, websites, and relevant journals. Results & Conclusion: Different types of Agada Yogas mentioned in Vishchikitsa Granthas, some of them are Bilwadi Agada, Mahagada, Dushivishari Agada, Dashanga Agada and Sanjivana Agada. From various types of studies, books, and relevant journals we got to know that these Agada Yogas possess antitoxic properties and was very effective in elimination of poisons from the body. In current scenario, there are many diseases that are happen due to different types of preservatives, artificial poisons we are using in our current day to day lives. These Agada Yogas are the mixture of antitoxic medications act as an immunomodulator, antioxidants and some of them possess hepatoprotective action also. The Ushna(hot potency), Teekshna(sharp) and vyavayi (rapid spreading) qualities of Agada Yogas aid in the eradication of various poisons from the body. These Yogas are more effective due to its Vishaghna ingredients and Prabhav.